ТЕОРІЯ ТА ПРАКТИКА УПРАВЛІННЯ ЯКІСТЮ ТА ЇХ ВПЛИВ НА СУЧАСНІ КОНЦЕПЦІЇ ПІДПРИЄМНИЦТВА - Kalinichenko, Olena (Zhytomyr Ivan Franko State University, 2025)
The presented article analyses the existing approaches to the optimisation of quality management systems in the context of modern product policy of the enterprise. The author substantiates the thesis about the dynamic nature of quality management systems operating at enterprises due to the processes of market globalisation, which necessitates their continuous improvement. The main vectors of improvement of quality management systems at enterprises are defined taking into account such characteristics of global markets as high level of competition, consumer awareness and volatility of market conditions. TQM is based on the idea of continuous development, maintenance and improvement of quality characteristics of service and production processes of companies operating in the market of goods and services. The key objective of this approach is to maximise customer satisfaction in the current market conditions. It should be noted that, like any other conceptual framework or model, TQM has both advantages and disadvantages. it was noted that TQM is a customer centred process that aims to continuously improve the management of all aspects of business operations. The key is to involve all employees in the common goal of improving the quality characteristics of products/services and improving production procedures. This is why there is a specific set of guidelines that help to embed this concept into the practices of the company. Considering the fact that the modern Total Quality Management approach differs significantly from traditional quality assurance methods, their underlying principles are analysed according to certain criteria. It is proven that establishing TQM is a continuous journey, and although the initial or ongoing investment may seem significant, it is capable of producing tangible benefits in the long term through consistent efforts by the organisation. These efforts require considerable energy, close attention from top management, substantial financial investment, stamina and steadfastness in decision making and implementation. It should be realised that even the best improvement plan will be meaningless without implementation. With this in mind, it can be argued that TQM is a flexible concept that can be successfully implemented by companies and businesses in a variety of industries, despite its initial application in the manufacturing sector. It has the advantage of providing a holistic view of the necessary systemic changes with a focus on achieving long-term strategic goals rather than short-term gains. The actual use of TQM in many sectors of the economy, such as manufacturing, banking and finance, and medicine, confirms its versatility. Quality is an extremely important aspect of any business and cannot be underestimated if a company is to remain competitive in the marketplace. The importance of quality can be traced back to almost every stage of the production process, and this is what TQM is aimed at - constant monitoring, careful analysis and continuous improvement.